2015
DOI: 10.1248/bpb.b14-00640
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Drug Treatment Increases Intestinal Bile Acid Absorption <i>via</i> Elevated Levels of Ileal Apical Sodium-Dependent Bile Acid Transporter but Not Organic Solute Transporter α Protein

Abstract: Antibacterial drug treatment increases the bile acid pool size and hepatic bile acid concentration through the elevation of hepatic bile acid synthesis. However, the involvement of intestinal bile acid absorption in the increased bile acid pool size remains unclear. To determine whether intestinal bile acid absorption contributes to the increased bile acid pool in mice treated with antibacterial drugs, we evaluated the levels of bile acid transporter proteins and the capacity of intestinal bile acid absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…4-7). These findings are consistent with previous studies (Sayin et al, 2013;Hu et al, 2014;Miyata et al, 2015;Selwyn et al, 2015b). T-CA was increased in all compartments, except liver.…”
Section: Discussionsupporting
confidence: 93%
“…4-7). These findings are consistent with previous studies (Sayin et al, 2013;Hu et al, 2014;Miyata et al, 2015;Selwyn et al, 2015b). T-CA was increased in all compartments, except liver.…”
Section: Discussionsupporting
confidence: 93%
“…The ileal BA uptake transporter (Asbt) is thought to be responsible for the reabsorption of most of the BAs from the intestine (Dawson et al, 2003). It is known that antibiotics decrease the number of intestinal bacteria, increase intestinal BA absorption (Miyata et al, 2015), decrease fecal BA excretion, and increase hepatic BA concentrations (Hu et al, 2014;Zhang et al, 2014), with an increase in ileal Asbt expression. On the contrary, Asbt-null mice have limited enterohepatic circulation of BAs, increased fecal BA excretion, and decreased BA pool size (Dawson et al, 2003), which is just the opposite of what is observed in GF mice.…”
Section: Discussionmentioning
confidence: 99%